2009
DOI: 10.1080/02827580903280053
|View full text |Cite
|
Sign up to set email alerts
|

Estimating breast height diameter and volume from stump diameter for three economically important species in Turkey

Abstract: Predicting volume directly from stump dimensions is useful in many situations, such as timber trespass. In the present study, equations for predicting diameter at breast height (dbh) and tree volume from stump diameter outside bark were developed for three economically important tree species in the forest region of Bucak, Turkey. Diameter at breast height was estimated with relatively high accuracy using a simple linear model. Tree volume was estimated with high precision using an exponential equation. Weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Equivalence test looks for similarities while the usual hypothesis test looks for differences. The conclusion of no statistically significant difference of the usual statistical test means that the current evidence is not strong enough to support that the examined treatments lead to different outcomes (Robinson et al, 2005;Özçelik et al, 2010). That is different from saying that the two outcomes are the same.…”
Section: Equivalence Testingmentioning
confidence: 70%
“…Equivalence test looks for similarities while the usual hypothesis test looks for differences. The conclusion of no statistically significant difference of the usual statistical test means that the current evidence is not strong enough to support that the examined treatments lead to different outcomes (Robinson et al, 2005;Özçelik et al, 2010). That is different from saying that the two outcomes are the same.…”
Section: Equivalence Testingmentioning
confidence: 70%
“…Previous studies have shown that tree crown diameter (Cd) is well correlated with tree bole diameter (Kigomo, 1991;Gering and May, 1995;Kigomo, 1998;Lockhart et al, 2005;Hemery et al, 2005). In the same vein, stump diameter (Dst) is highly correlated with diameter at breast height (Dbh), and as such have being used in place of Dbh to predict most tree growth variable especially in the case of illegal logging (Osho, 1983;Westfall, 2010;Özçelík et al, 2010;Shamaki and Akindele, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating DBH of trees from stump dimension may help to reconstruct silvicultural practices and to assess harvested timber and wood, when pre-operation data are not available. Pre-operation data are surely not available in case of illegal cuttings, and estimating DBH is the only way to assess the loss, through a two-step procedure (Corral-Rivas et al 2007, Özçelík et al 2010, unless volume functions based on stump information are available. Another application of diameter prediction occurs when a harvest crosses ownership boundary (Chhetri et al 1996, Pond andFroese 2014).…”
Section: Introductionmentioning
confidence: 99%